Determinants of brand loyalty and the link between brand loyalty and price tolerance - Tümer, Ebru; Aygün, Inci (Bogazici Universitesi, 2007)
The aim of this study is to investigate the integrated relationships between brand satisfaction, brand trust and brand affect through the brand loyalty development process and price tolerance as an outcome of the brand loyalty process. Data are collected based on a survey of 1085 students from various universities in Istanbul, Turkey. The findings indicate that brand affect and brand trust are key constructs in the brand loyalty formation process. Brand satisfaction is effective on brand loyalty indirectly through strengthening these constructs. Additionally, brand loyalty is a strong antecedent of consumers' tolerance to price. The research findings will help provide clarification on how brand loyalty comes about and brings about price tolerance. © 2018 Elsevier B.V., All rights reserved.
Keywords: Brand affect and price tolerance; Brand loyalty; Brand satisfaction; Brand trust